2015
DOI: 10.1007/s11255-015-1022-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between arterial stiffness and inflammatory markers in autosomal dominant polycystic kidney disease patients with preserved renal function

Abstract: In conclusion, our findings revealed increased PTX3 levels and reduced SAEI in patients as compared with controls, while no correlation between inflammatory markers studied and the small artery elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…NLR has also been associated with arterial stiffness and high coronary calcium score in several previous studies ( 48 ). Early detection of abnormal NLR levels may be helpful for detecting increased arterial stiffness in patients with coronary heart disease, type 1 and 2 diabetes mellitus, osteoporosis, and polycystic kidney disease (Table 2 ) ( 19 , 44 , 66 , 67 , 69 , 75 ).…”
Section: Wbcs and Arterial Stiffnessmentioning
confidence: 99%
“…NLR has also been associated with arterial stiffness and high coronary calcium score in several previous studies ( 48 ). Early detection of abnormal NLR levels may be helpful for detecting increased arterial stiffness in patients with coronary heart disease, type 1 and 2 diabetes mellitus, osteoporosis, and polycystic kidney disease (Table 2 ) ( 19 , 44 , 66 , 67 , 69 , 75 ).…”
Section: Wbcs and Arterial Stiffnessmentioning
confidence: 99%
“…The neutrophil–lymphocyte ratio (NLR) is a biomarker that reflects the inflammation status of the human body [10] as well as the balance between activation and regulatory factors of inflammation [11]. Several studies have found that NLR is associated with malignant tumors [12], coronary artery disease [13], atherosclerosis [14], heart failure [15], acute pancreatitis [16], diabetes [17], obesity and dyslipidemia [18], hypertension [19], metabolic syndrome (MetS) and endothelial dysfunction [20], osteoporosis [21], and polycystic kidney disease [22,23]. Researchers have increasingly realized the importance of NLR in the progression of ACS.…”
Section: Introductionmentioning
confidence: 99%